Laparoscopic splenectomy for splenic abscess secondary to infective endocarditis - Almada, Mario; Bonilla, Fernando; Martínez, José; Pouy, Andrés; Misa, Ricardo (Cirugía del Uruguay, 2020)
Splenic abscess is a rare clinical entity that is most often associated with infective endocarditis. Heart valve replacement in the setting of an untreated splenic abscess is associated with a high incidence of prosthetic valve infection and death. A patient with infectious endocarditis and splenic abscess treated by laparoscopic splenectomy followed by valve replacement is described.